Linguistic and Stylistic Features of the Dialogue in the Early Novels of M. Vargas Llosa - B. V. Kovalev (Ибероамериканские тетради)
The article analyzes the poetics of dialogue in the so-called «first-style» novels of M. Vargas Llosa: «The Time of the Hero» (1963), «The Green House» (1966) and «Conversation in The Cathedral» (1969). The study of the linguo-stylistic specifics of dialogues in Latin American texts is especially relevant, because it is in the poetics of the total novel during the Latin American boom that dialogue is the key technique. The methodology of the study is based on the works of B.C. Prado, A.N. Veselovsky and V.V. Vinogradov, in particular, the method of classifying dialogues in fiction of the 20th century. There are three types of dialogues that can be distinguished in the early novels of M. Vargas Llosa: traditional dialogue, monologized dialogue and dialogized monologue. It turns out that the traditional dialogue is characterized by the division of replicas into lines and the sequence of the dialogue without nonchronological fragments and introspection. The monologized dialogue is written in a line: it is based on the principle of repetition / parallelism and is characterized by rhythmicity. The dialogized monologue is a combined type of two dialogues, which are external (extradiegetic) and internal (intradiegetic). At the external level, two actants report information about an event, whereas at the internal level, the event itself is updated. As a result, we conclude that in the novel «The Time of the Hero» the three types of dialogues are at an early stage of their development, «The Green House» turns out to be a novel in which all three types of dialogue are smoothly and harmoniously combined, and in «Conversation in The Cathedral» the dialogized monologue becomes structure-forming and dominant technique.